Combined transcriptomic and physiological metabolomic analyses elucidate key biological pathways in the response of two sorghum genotypes to salinity stress - Zhang, Fei; Lu, Feng; Wang, Yanqiu; Zhang, Zhipeng; Wang, Jiaxu; Zhang, Kuangye; Wu, Han; Zou, Jianqiu; Duan, Youhou; Ke, Fulai; Zhu, Kai (Frontiers in Plant Science, 2022)
Sorghum is an important food crop. Compared with other crops, its salt tolerance is stronger. Therefore, studying the salt tolerance mechanism of sorghum has great significance for understanding the salt tolerance mechanism of C4 plants. In this study, two sorghum species, Baye Qi (salt-tolerant, ST) and Pl212 (salt-sensitive, SS), were treated with high-concentration salt solution and the plant physiological indicators were measured. Transcriptomic and metabolomic analysis were performed by Illumina sequence and Liquid Chromatography-Mass Spectrometry (LC-MS) technology, respectively. The results showed that the plant height, leaf area and chlorophyll contents in Baye Qi were significantly higher than that of Pl212. The differently expressed genes (DEGs) functional analysis showed that Plant hormone signal transduction (sbi04075), carbohydrate catabolic process (GO:0016052) and photosynthesis (GO:0015979) were the main pathways response to salt stress in sorghum. The genes of the two varieties show different expression patterns under salt stress conditions. The metabolomic data revealed the different profiles of salicylic acid and betaine between Baye Qi and Pl212, which mediated the salt tolerance of sorghum. In conclusion, Baye Qi Sorghum response to salt stress via a variety of biological processes, including energy reserve, accumulation of salicylic acid and betaine, and improving the activity of salt stress-related pathways, etc.